MiR-205/IRAK2 signaling pathway is associated with urban airborne PM2.5-induced myocardial toxicity. Issue 9 (20th October 2020) - Feng, Lin; Wei, Jialiu; Liang, Shuang; Sun, Zhiwei; Duan, Junchao
Abstract: Exposure to fine particulate matter (PM2.5 ) is closely linked with cardiovascular diseases. However, the underlying mechanism of PM2.5 on cardiac function remains unknown. This study was aimed to investigate the role of microRNA-205 (miR-205) on PM2.5 -induced myocardial inflammation and cardiac dysfunction. PM2.5 increased the levels of reactive oxygen species (ROS) and malondialdehyde (MDA), following by decreased cell viability and antioxidant enzymes, resulting in apoptosis of cardiomyocytes (AC16). The histopathological and ultrastructural analysis demonstrated that PM2.5 caused myocardial damage via interstitial edema, inflammatory cell infiltration, and myocardial fiber destruction. PM2.5 enhanced the release of inflammatory factors in AC16 cells and heart tissue. Microarray analysis and dual-luciferase reporter gene assays demonstrated that PM2.5 -induced down-regulation of miR-205 regulated interleukin 1 receptor-associated kinase 2 ( IRAK2 ), which further activated the TNF receptor-associated factor 6 (TRAF6)/nuclear transcription factor-κB (NF-κB) signaling pathway in vivo . Moreover, the chemical mimics of miR-205 markedly inhibited the IRAK2/TRAF6/NF-κB signaling pathway, whereas the chemical inhibitors of miR-205 amplified PM2.5 -induced activation of the IRAK2 signaling pathway in vitro . In summary, our results found that PM2.5 could trigger myocardial toxicity via miR-205 negative regulating the IRAK2/TRAF6/NF-κB signaling pathway. Our study suggests that miR-205 could be a promising target molecule for mitigating the hazardous effects of PM2.5 on the cardiovascular system.